The Impact Of Exchange Rates And Interest Rates On Coal Mining Company Stock Prices Through Profitability - Tuti Fitriani; Abu Bakar (Politeknik Siber Cerdika Internasional, 2025)
Fluctuations in exchange rates and interest rates in a dynamic economic environment mean that coal mining companies need to carefully monitor, identify and respond to these changes with appropriate strategies, in order to minimize risks and increase profitability and the company's stock price. This research explores the influence of exchange rates and interest rates on stock prices of coal mining companies through profitability as an intermediary variable. The research method used is an associative method with a sample consisting of 20 coal mining companies listed on the Indonesia Stock Exchange, which were selected through a purposive sampling technique. To achieve the objectives of this research, path analysis was applied to time series data for 2013-2022, obtained from the Indonesian Stock Exchange and Bank Indonesia. The results of this research show that exchange rates and interest rates have a significant influence on company stock prices directly. Meanwhile, profitability is unable to mediate the influence of exchange rates and interest rates on stock prices. This research provides important insights for mining company managers, enabling them to understand the impact of macroeconomic factors, such as exchange rates and interest rates, on stock prices.